Looking Back in Anger? Retirement and unemployment scarring - Clemens Hetschko; Andreas Knabe; Ronnie Schöb (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Previous studies find that past unemployment reduces life satisfaction even after reemployment for non-monetary reasons (unemployment scarring). It is not clear, however, whether this scarring is only caused by employment-related factors, such as worsened working conditions, or increased future uncertainty as regards income and employment. Using German panel data, we identify non-employment-related scarring by examining the transition of unemployed people to retirement as a life event after which employment-related scarring does not matter anymore. We find evidence for non-employment-related non-monetary unemployment scarring for people who were unemployed for the first time in their life directly prior to retirement, but not for people with earlier unemployment experiences.
Keywords: I31; J26; 330; unemployment scarring; life satisfaction; retirement